Rapid Geomorphic and Habitat Stream Assessment Techniques Inform Restoration Differently Based on Levels of Stream Disturbance1. (5th March 2014) - Habberfield, Michael W.; Blersch, Stacey Sloan; Bennett, Sean J.; Atkinson, Joseph F.
Abstract Visual‐based rapid assessment techniques provide an efficient method for characterizing the restoration potential of streams, with many focusing on channel stability and instream habitat features. Few studies, however, have compared these techniques to see if they result in differing restoration priorities. Three rapid assessment techniques were contrasted at three wild trout streams in western New York with different amounts of channel disturbance. Two methods focused only on geomorphic stability, whereas the third addressed physical habitat condition. Habitat assessment scores were not correlated with scores for either geomorphic assessment method and they varied more between channels with different degrees of disturbance. A model based on dynamic equilibrium concepts best explains the variation among the streams and techniques because it accounts for a stream's capacity to maintain ecological integrity despite some inherent instability. Geomorphic indices can serve as effective proxies for biological indices in highly disturbed systems. Yet, this may not be the case in less disturbed systems, where geomorphic indices cannot differentiate channel adjustments that impact biota from those that do not. Dynamically stable streams can include both stable and unstable reaches locally as characterized by geomorphic methods and translating these results into restoration priorities may not be appropriate if interpretations are limited to the reach scale.